2013
DOI: 10.1002/ps.3581
|View full text |Cite
|
Sign up to set email alerts
|

High levels of biological activity of Cry1Ac protein expressed on MON 87701 × MON 89788 soybean against Heliothis virescens (Lepidoptera:Noctuidae)

Abstract: The MON 87701 × MON 89788 soybean provides an effective alternative in controlling Heliothis virescens and complies with the concept of high-dose for IRM programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 28 publications
2
42
0
2
Order By: Relevance
“…Yu et al (2013) found in bioassays that soybean plants that express the Cry1Ac protein are highly resistant to H. armigera because of the insect's sensitivity to this toxic protein. Bernardi et al (2014) also observed complete mortality in 1st-to 5th-instar larvae of Heliothis virescens after they were exposed to the Bt soybean, showing the efficacy of this technology for control of lepidopterans feeding on this soybean cultivar.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Yu et al (2013) found in bioassays that soybean plants that express the Cry1Ac protein are highly resistant to H. armigera because of the insect's sensitivity to this toxic protein. Bernardi et al (2014) also observed complete mortality in 1st-to 5th-instar larvae of Heliothis virescens after they were exposed to the Bt soybean, showing the efficacy of this technology for control of lepidopterans feeding on this soybean cultivar.…”
Section: Discussionmentioning
confidence: 73%
“…Because this species feeds on several crops (Gunning et al, 2005), there is some risk that populations in Brazil might develop resistance to Cry 1Ac because the protein is present in both Bt soybean and Bt cotton, and successive planting of these cultivars might extend the period of pest exposure to the protein and hence increase the possibility of selecting resistant individuals (Bernardi et al, 2014). Therefore, a high degree of control of H. armigera in Bt soybean and consequent reduction of damage from this pest will be necessary to maintain the effective refuge areas, aiming toward the sustainability of the technology.…”
Section: Discussionmentioning
confidence: 99%
“…Bernardi et al (2014) and Bortolotto et al (2014) assessed the larval biology of H. virescens in genetically modified soybean plants (Bt) and concluded that the pest is highly susceptible, thereby suffering larval mortality. The lower consumption indexes in this cultivar are due to the presence of toxins from Bacillus thuringiensis (Eubacteriales: Bacillaceae), which induce the formation of endotoxins (Waquil et al, 2002) poisonous to insects, especially lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
“…This insect is a facultative migratory pest that can fly long distances in search of its host plants (Farrow and Daly, 1987). Inappropriate insecticide applications and their undesirable effects as well as the selection of individuals resistant not only to chemical insecticides but also to transgenic plants (Blanco et al, 2009;Sosa-Gomez and Silva, 2010;Bernardi et al, 2014;Bortolotto et al, 2014) lead to the need to investigate alternative pest control methods and strengthen integrated pest management (IPM) (Bueno et al, 2011a). Among the alternative methods, the exploitation of plant resistance to insects is considered ideal because this approach does not affect the environment, may be concomitantly used with other control methods, and does not require producers to deal with sophisticated technology (Smith, 2005;Seifi et al, 2013;Boiça Junior et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This insecticidal protein has also been shown to be efficacious in controlling H. virescens larvae in soybean and cotton (Terán-Vargas, 2005;Bortolotto et al, 2014). In soybean, even in more developed plants (withseed pods), the concentration of the insecticidal protein is sufficient to control H. virescens larvae (Bernardi et al, 2013;Bortolotto et al, 2014) (Table 5).…”
Section: Seed Treatment In Cry1ac Soybeanmentioning
confidence: 99%